A cry for help how to help a friend who is depressed or suicidal - Spatzeck-Olsen, Charity; Spatzeck-Olsen, Hans; Aquarius Health Care Videos; Paraclete Video Production (Brewster, MA: Paraclete Video Production [production company] ; Sherborn, MA : Aquarius Production [distributor], 2001)
Discussed about how to intervene and get help when a friend is contemplating suicide
Executive producer, Lilian Miao, Carol Showalter, Robert Edmonson
Narrator: Stew Herrara
DVD format
Keywords: Suicide -- Prevention; Suicide -- psychology; Suicide -- Psychological aspects; Teenagers -- Suicidal behavior; Suicide -- prevention & control